A witches' ball [videorecording (DVD)] - Dyck, Justin G.; McBrearty, Patrick; Cooper, Keith; Buzora, Martin; Stadtlander, Elizabeth; Mason, Paul; Slater, Karen; Stein, Renée; Neundorf, Morgan; Steinberg, David, 1962- (Dreamscape Media, 2025)
A young witch is ready to jump feet first into the witching world but not before leaping over some magical hurdles along the way.